2008
DOI: 10.1002/hyp.7197
|View full text |Cite
|
Sign up to set email alerts
|

Hydroecological response of river systems to shrinking glaciers

Abstract: Abstract:Aquatic ecosystems in high latitude and altitude environments are strongly influenced by cryospheric and hydrological processes due to links between atmospheric forcing, snowpack/glacier mass-balance, river discharge, physico-chemistry and biota. In the current phase of global climate warming, many glaciers are shrinking. Loss of snow and ice-masses will alter spatial and temporal dynamics in bulk basin runoff with important changes in the relative contributions of snowmelt, glaciermelt and groundwate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
300
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(309 citation statements)
references
References 133 publications
(162 reference statements)
8
300
1
Order By: Relevance
“…More specifically, the loss of a number of endemic, glacier stream specialists is likely to occur , particularly in basins fed by small glaciers such as the Taillon and the Mutt. This will lead to a reduction in basin and regional scale diversity (Jacobsen et al, 2012) despite a predicted increase in alpha (site) diversity as water source contributions change (Milner et al, 2009). This highlights the need for careful consideration regarding how biodiversity is measured and interpreted in the context of conservation, particularly in alpine environments where between site diversity and range restricted, endemic taxa are important components of regional biodiversity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, the loss of a number of endemic, glacier stream specialists is likely to occur , particularly in basins fed by small glaciers such as the Taillon and the Mutt. This will lead to a reduction in basin and regional scale diversity (Jacobsen et al, 2012) despite a predicted increase in alpha (site) diversity as water source contributions change (Milner et al, 2009). This highlights the need for careful consideration regarding how biodiversity is measured and interpreted in the context of conservation, particularly in alpine environments where between site diversity and range restricted, endemic taxa are important components of regional biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…As benthic assemblages in high headwater alpine streams appear strongly deterministic, especially in highly glacial reaches where environmental filtering is particularly strong (Castella et al, 2001), habitat template changes can be used to predict how biodiversity and ecosystem functioning will respond (Fig.4). Changes in glacier cover/meltwater contribution can be used as a surrogate for the suite of environmental parameters which dictate macroinvertebrate community structure (Milner et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DOC encompasses a large pool of molecules, which depending on their source (i.e., autochthonous versus allochthonous), can vary in chemical composition and bioavailability (e.g., Sun et al, 1997;JaffĂ© et al, 2012). Allochthonous constituents typically dominate the DOC pool, with the exception of alpine and arid catchments devoid of major terrestrial vegetation (e.g., Milner et al, 2009). In alpine streams, autochthonous deliveries from algal production (and mosses) characterise DOC in streams above the treeline, whereas terrestrial deliveries increasingly add to the carbon pool further downstream (Battin et al, 2004;Milner et al, 2009;Zah and Uehlinger, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Allochthonous constituents typically dominate the DOC pool, with the exception of alpine and arid catchments devoid of major terrestrial vegetation (e.g., Milner et al, 2009). In alpine streams, autochthonous deliveries from algal production (and mosses) characterise DOC in streams above the treeline, whereas terrestrial deliveries increasingly add to the carbon pool further downstream (Battin et al, 2004;Milner et al, 2009;Zah and Uehlinger, 2001). Several studies have reported DOC source and composition as potential drivers of microbial community structure and functioning in streams (e.g., Kaplan and Bott, 1989;Sun et al, 1997;Peter et al, 2011) and in lakes (e.g., Crump et al, 2003;Judd et al, 2006).…”
Section: Introductionmentioning
confidence: 99%